1995
DOI: 10.1016/0304-3959(94)00097-x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in plasma calcitonin gene-related peptide from the extracerebral circulation during nitroglycerin-induced cluster headache attack

Abstract: In this study, changes in plasma levels of calcitonin gene-related peptide (CGRP) and substance P (SP) during a spontaneous-like cluster headache attack provoked by nitroglycerin were evaluated. Peptide variations after spontaneous or sumatriptan-induced remission were also assessed. Blood was collected from the external jugular vein homolateral to the pain side of 30 male cluster headache patients; 18 men were in an active and 12 in a remission one. Plasma levels of CGRP and SP were determined using sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
169
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(186 citation statements)
references
References 31 publications
14
169
1
2
Order By: Relevance
“…This is in concert with the facial symptoms of this disorder. The findings agree well with the results of others [52] demonstrating release of CGRP in nitroglycerin-elicited attacks of cluster headache. Fanciullacci et al [53] observed in another study that nitroglycerin could only elicit an attack of cluster headache with CGRP release if the patient was in a latent period and thus prone to activation.…”
Section: Cluster Headachesupporting
confidence: 93%
“…This is in concert with the facial symptoms of this disorder. The findings agree well with the results of others [52] demonstrating release of CGRP in nitroglycerin-elicited attacks of cluster headache. Fanciullacci et al [53] observed in another study that nitroglycerin could only elicit an attack of cluster headache with CGRP release if the patient was in a latent period and thus prone to activation.…”
Section: Cluster Headachesupporting
confidence: 93%
“…*p Ͻ 0.05. ric [Ca 2ϩ ] i measurements revealed involvement of SNAP-25 in spontaneous and evoked CGRP exocytosis, with important implications for synaptic communication between trigeminal sensory neurons. In light of the well established proinflammatory activity of CGRP and its direct involvement in migraine (Fanciullacci et al, 1995;Doods et al, 2007), our data yield new information pertinent to the mechanism of chronic pain and provide a scientific basis for using BoNT variants as therapeutics for chronic pain and neuroinflammatory disorders.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, BIBN4096BS could produce, at a postjunctional level (by CGRP receptor blockade), effects similar to those that triptans cause by reducing CGRP release, and that result in inhibition of CGRP receptor signalling. Indeed, triptans inhibit trigeminal CGRP release in animal experimental models [55,63], and clinical data show that sumatriptan normalised the elevated CGRP levels with alleviation of migraine [55] and cluster headache attack [65]. These findings have suggested that BIBN4096BS could be developed as an effective antimigraine drug.…”
Section: Cgrp Antagonists In Migrainementioning
confidence: 97%
“…A Ca 2+ -dependent and capsaicin-sensitive release of CGRP, but not SP, has been documented from human tissues containing non-trigeminal [13] or trigeminal [11] sensory nerve endings. Furthermore, plasma concentrations of CGRP, but not of SP, were elevated during the headache phase of migraine [64] and cluster headache [65]. There is evidence that intravenous infusion of CGRP produces a migraine-like headache [66], and intravenous infusion of nitric oxide produces a migraine-like headache with an associated increase in plasma CGRP levels [67].…”
Section: Migraine and Neurogenic Inflammationmentioning
confidence: 99%